2023
DOI: 10.1097/upj.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Bladder and Kidney Cancer Diagnosis and Survival Increase With Medicare Eligibility at Age 65

Abstract: Introduction:Medicare eligibility at 65 has been associated with increased diagnosis and survival for certain cancers due to greater health care utilization. We aim to assess for a similar “Medicare effect” for bladder and kidney cancers, which has not been previously established.Methods:Patients diagnosed with bladder or kidney cancer from 2000-2018 at ages 60-69 years were identified with the Surveillance, Epidemiology, and End Results database. We used age-over-age percent change calculations to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The disproportionate impact of LPP on the elderly was found in Caucasians as well as Black, Asian, and Hispanic patients. This may indicate a higher LPP prevalence among this age group or reflect diagnostic delays due to limited health care access in underrepresented populations, potentially mitigated upon becoming Medicare‐eligible 4 …”
Section: Group Total Population N (%) Lpp Cases N Prevalence % (95% Ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…The disproportionate impact of LPP on the elderly was found in Caucasians as well as Black, Asian, and Hispanic patients. This may indicate a higher LPP prevalence among this age group or reflect diagnostic delays due to limited health care access in underrepresented populations, potentially mitigated upon becoming Medicare‐eligible 4 …”
Section: Group Total Population N (%) Lpp Cases N Prevalence % (95% Ci)mentioning
confidence: 99%
“…underrepresented populations, potentially mitigated upon becoming Medicare-eligible. 4 A Brazilian study demonstrated a negative association between cigarette smoking and frontal fibrosing alopecia (FFA), a subtype of LPP, hypothesizing that cigarette smoking leads to reduced production of interleukin (IL)-12 and IL-23 by dendritic cells and a shift towards T helper-2 response. 3 Additionally, the LPP/FFA pathogenesis has been linked to overexpression of the aryl hydrocarbon receptor (AhR), whereas cigarette smoking suppresses AhR expression to regulate cigarette smoke-induced oxidative stress.…”
mentioning
confidence: 99%